Probes and Targets of DNA Methylation and Demethylation in Drug Development - Mirfattah, Barsam; Herring, Jason; Tang, Hui; Zhang, Kangling (Current Topics in Medicinal Chemistry, 2017)
DNA methylation and demethylation is part of the essential biological processes regulating gene expression in normal cell development. Abnormal methylation status of specific genes and their irregularly translated proteins are normally associated with certain kinds of diseases or cancer. The rapid development of innovative DNA methylation mapping techniques provides a better understanding of DNA methylation pattern and its mechanisms in the human genome and its correlation with numerous diseases. These new techniques can lead us to develop new epigenetic medications, such as DNA methyltransferase inhibitors. As part of the approaches to probe DNA methylation and evaluate the effects of epigenetic therapy, mass spectrometry has been taking an important role in the identification, validation, and quantification of DNA methylation and demethylation. In this review, we will briefly summarize the current breadth of knowledge on the topic of DNA methylation and its occurrence in diseases, DNA methylation drugs, and mass spectrometry based approaches used to study DNA methylation.
Keywords: mass spectrometry